Vocabulary learning strategies for the development of EFL reading skills among 10th graders at Lemas school. - Proaño Proaño, Robert Andrés (2022)
The development of students' varied academic duties is aided by their ability to read comprehension, which is a crucial talent. It aids children in text analysis, explanation, and the expression of their own opinions regarding written materials. Learning to read and comprehend written information is a skill that students need to master in order to succeed in the academic work that their teachers assign them. If students wish to become proficient readers, one of the main goals of reading comprehension is to help them develop their reading abilities and comprehension of texts. The foundation of learning a second language is vocabulary, and the level of success in learning any language depends on the learner's vocabulary knowledge. Understanding vocabulary helps one master language abilities (reading, listening, writing, and speaking). There are numerous reading strategies that can be used to help students become better readers and better grasp given texts. Reading comprehension of students has a significant part in how EFL (English as a foreign language) learner interact with the text. Furthermore, some characteristics have a discernible impact on reading comprehension. Language internationalization is inevitable given the march toward globalization. The most significant role will probably be played by English. Grammar, vocabulary, and pronunciation are all included. Vocabulary is without a doubt the most vital and dynamic of the three components. The results of this review paper showed that effective reading methods are essential for raising reading comprehension in EFL students.